Ensayos de política económica - Pontificia Universidad Católica Argentina Santa María de los Buenos Aires. Departamento de Investigación Francisco Valsecchi (Pontificia Universidad Catolica Argentina, 2007)
Devoted to research and scholarship in economic and social policy, covering areas such as macroeconomics, international economics, monetary economics, financial economics, fiscal policies, growth, development, history of economic policy, institutions, economic regulation, industrial organization, social policies, labor market, poverty and income distribution, among others.
Keywords: Economic policy : Periodicals; Social policy : Periodicals; Economic policy; Social Policy